Comparative Efficacy of Different Fixed Drug Combinations on Clinical Signs of Respiratory Disease in Starter Pigs - Habawel, Candice Mabette; Purnamasari, Listya; Olarve, Joseph Peñano; dela Cruz, Joseph Flores (Jurnal Veteriner; Vol 23 No 3 (2022), 2022)
The high occurrence of respiratory disease in pigs has led to the innovation of fixed-dose drug combinations (FDCs). A study was conducted to determine the efficacy of two FDCs on 15 starter pigs showing clinical signs of respiratory disease to determine its effect on their respiratory health and growth. Treatment 1 (T1) was the control group and did not receive any medication. Treatment 2 (T2) contains 90 g of Doxycycline, 40 g of Tylosin, 30 g of Paracetamol, 5 g of Bromhexine, and 500 mg of Prednisolone as active ingredients per kilogram. Treatment 3 (T3) contains 150 g of Amoxicillin Trihydrate, 100 g of Tylosin Tartrate, and 5 g of Bromhexine Hydrochloride as active ingredients per kilogram. The treatment gives at a therapeutic dose of 10 g/gallon of water twice a day for 7 days.The effects of FDCs were measured through clinical sign evaluation, gross pathologic lung lesion scoring, histopathologic examination, and evaluation of the production performance of the starter pigs using analysis of variance (ANOVA) for a Completely Randomized Design. Pigs treated with Treatment 2 had better clinical evaluation scores and production performance than Treatment 3. Histopathologic examination demonstrated minimal tissue repair in all FDCs studied. Improvement denotes that the treatment produces a positive effect.